ATENDIMENTO E TRATAMENTO ÀS PESSOAS QUE FORAM ATINGIDAS PELA HANSENÍASE – A PARTIR DO GRUPO DE APOIO NO MUNICÍPIO DE PONTA GROSSA – PR - Santos, Aparecida Garcia dos (2016)
Leprosy is a sickness that has been around for thousands of years, and since the biblical times has always been a focus of various discussions. For a long time, a person infected with leprosy was isolated from society, excluded, as well as called leper, unclean, dirty, and a sinner. In this sense, Leprosy became a sickness marked with stigma and discrimination, and those inflicted suffered from such. The objective study is to comprehend the structure of the Support Group of Patients with Leprosy (GAPHAN) while group action gives support to the public politics of health for lepers in the process of being attended. Developed in the City of Ponta Grossa – PR, in the Specialized Assistance Service (SAE), with professionals and participants of GAPHAN. This research is a descriptive and explorative work. Quality study was utilized, accomplished through semi-structured interviews with oral testimonies and non-participant observation, together with the participants of the research. The research was founded in bibliographical and documental study. The results of this research give evidence that the action of the support group strengthen the attendance and treatment of those with leprosy, in the city of study. This study made possible the understanding of the universe of meanings understood by the word leper, and gave evidence of the stigma, as explained by Goffman. The activities and happenings of GAPHAN aid in the attendance and precocious detection of leprous cases of relatives. Group co-living aids in the elevation of self-confidence, cognitive development, self-care and contributes to the reintegration of lepers into society, giving support to the public politics of health for lepers. In this sense, the group becomes a support for the control program and elimination of leprosy in the city of Ponta Grossa – PR.